Chikungunya virus infection induces ultrastructural changes and impaired neuronal differentiation of human neurospheres - de Lima Cavalcanti, Thaíse Yasmine Vasconcelos; Azevedo, Elisa de Almeida Neves; Lima, Morganna Costa; Saraiva, Karina Lidiane Alcântara; Franca, Rafael Freitas Oliveira (Frontiers in Microbiology, 2023)
Chikungunya virus (CHIKV) is an arthropod-borne virus recently associated with large outbreaks in many parts of the world. Infection is typically manifested as a febrile and self-limited illness, characterized by joint pain and myalgia, albeit severe neurological manifestations are also reported. Although CHIKV is not recognized as a truly neurotropic virus, neurons, astrocytes, and oligodendrocytes are susceptible to infection in vitro. Here we employed a model of 3D cell culture to obtain neurospheres from ATRA/BNDF differentiated human neuroblastoma cells. We demonstrate that CHIKV is able to establish a productive infection, resulting in ultrastructural changes in cell morphology and impaired neuronal differentiation. Ultrastructural analysis of neurospheres infected with CHIKV during neuronal differentiation revealed diminished neuron dendrite formation, accumulation of viral particles associated with the plasma membrane, numerous cell vacuoles, and swollen mitochondria. Apoptotic cells were significantly increased at 72 hours post-infection. Compared to Zika virus, a well-characterized neurotropic arbovirus, CHIKV infection resulted in a more discrete, albeit detectable upregulation of IL-6 levels. Finally, we found that CHIKV infection resulted in an altered profile expression, mainly downregulation, of a group of transcription factors named Hox genes. Altogether our findings highlight important features of CHIKV in the CNS, as well as the feasibility of neurospheres as robust experimental models that can support further studies for novel pharmacological interventions.